The redistribution of freedom: Normative analysis of the universal basic income - Albert Juan-Francisco (Panoeconomicus)
Given the rapid structural changes that our societies are experiencing, there is an urgent need to rethink our values and reformulate the social contract. The Universal Basic Income (UBI) is gaining more relevance in academic and public debates as the best alternative for a necessary change. This paper presents an exhaustive evaluation of the UBI in its normative character with an assessment of its convenience according to different theories of social justice and concepts of freedom. It is argued that UBI can be a good tool to improve the freedom and well-being of individuals, but it is not exempt from criticism. The paper puts forward an original financing proposal through the creation of a Sovereign Wealth Fund and a new monetary policy design with the aim of minimizing these criticisms.